2022
DOI: 10.1155/2022/2442603
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Candida Infection and Serious Infections in Patients with Moderate-to-Severe Psoriasis Receiving Biologics: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Biological agents used to treat moderate-to-severe plaque psoriasis have been associated with Candida infection and other serious infections. It is, however, necessary to verify whether biologic agents increase the risk of Candida infection and serious infections and whether these risks vary among biologics. Methods. PubMed, EMBASE, and Cochrane Library were searched for eligible randomized controlled trials (RCTs) from their inception to December 2021. Results from individual RCT were pooled using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Increased intestinal inflammation has been reported in patients with IBD treated with secukinumab or brodalumab, thus increasing disease severity 41. Similarly, various IL-17 biologics have been associated with increased numbers of Candida or upper respiratory tract infections in numerous different patient groups, further increasing patient morbidity 40 42. Psoriasis patients treated with brodalumab have experienced depression/anxiety linked with suicidal thoughts 43.…”
Section: Discussionmentioning
confidence: 99%
“…Increased intestinal inflammation has been reported in patients with IBD treated with secukinumab or brodalumab, thus increasing disease severity 41. Similarly, various IL-17 biologics have been associated with increased numbers of Candida or upper respiratory tract infections in numerous different patient groups, further increasing patient morbidity 40 42. Psoriasis patients treated with brodalumab have experienced depression/anxiety linked with suicidal thoughts 43.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, risankizumab, a selective anti-IL-23 antibody approved for the treatment of psoriasis, has been observed to induce mucocutaneous candidiasis in approximately 3.4% of cases ( 15 ). This interaction between candidiasis and IL inhibitors is a serious concern for patients undergoing treatment with such inhibitors ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is because these medications suppress the immune response, which is essential in fighting candidiasis (Davidson et al 2022 ). In a randomised, controlled trial of psoriasis patients treated with secukinumab (an IL-17 inhibitor), the incidence of oral candidiasis was higher in the secukinumab group compared to the placebo group (Feng et al 2022 ). Another research on individuals with rheumatoid arthritis receiving ixekizumab, another IL-17 inhibitor, revealed that the incidence of candidiasis was more significant in the ixekizumab group than in the placebo group (Ruggiero et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%